2009
DOI: 10.3319/tao.2008.01.21.01(f3c)
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Refractivity Profiles Retrieved from FORMOSAT-3/COSMIC Radio Occultation Soundings: Preliminary Results of Statistical Comparisons Utilizing Balloon-Borne Observations

Abstract: AB STRACTThe GPS ra dio occultation (RO) soundings by the FORMOSAT-3/COS MIC (Tai wan's Formosa Sat el lite Misssion #3/Con stel la tion Ob serv ing Sys tem for Me te o rol ogy, Ion o sphere and Cli mate) sat el lites launched in mid-April 2006 are com pared with high-res o lu tion bal loon-borne (ra dio sonde and ozonesonde) ob ser va tions. This pa per pres ents pre lim i nary re sults of val i da tion of the COS MIC RO mea sure ments in terms of refractivity through the tro po sphere and lower strato sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Between 30 and 40 km, a large difference of 8 K was found when compared to lidar observations. Hayashi et al (2009) also showed good comparisons between COSMIC RO and the radiosonde refractivity profiles with 1-2 % mean difference. Kishore et al (2009) performed a validation study using the operational stratospheric analyses including the National Centers for Environmental Prediction reanalysis (NCEP), the Japanese 25-year Reanalysis (JRA-25) and the United Kingdom Met Office (UKMO) datasets.…”
Section: Data and Analysismentioning
confidence: 69%
“…Between 30 and 40 km, a large difference of 8 K was found when compared to lidar observations. Hayashi et al (2009) also showed good comparisons between COSMIC RO and the radiosonde refractivity profiles with 1-2 % mean difference. Kishore et al (2009) performed a validation study using the operational stratospheric analyses including the National Centers for Environmental Prediction reanalysis (NCEP), the Japanese 25-year Reanalysis (JRA-25) and the United Kingdom Met Office (UKMO) datasets.…”
Section: Data and Analysismentioning
confidence: 69%
“…Between 30 and 40 km, a large di¤erence of 8 K was found when compared with lidar observations. Hayashi et al (2009) also showed good comparisons between COSMIC RO and the radiosonde refractivity profiles with 1-2% mean di¤er-ence. Kishore et al (2009) performed a validation study using the operational stratospheric analyses including the National Centers for Environmental Prediction-Reanalysis (NCEP), the Japanese 25-year Reanalysis (JRA-25), and the United Kingdom Met O‰ce (UKMO) data sets.…”
Section: Data and Analysismentioning
confidence: 71%
“…COSMIC refractivity precision is < 0.2% between 10–20 km and is 0.7% at 30 km [ Schreiner et al , 2007]. A positive bias of 1–2% between radiosondes and COSMIC was observed by Hayashi et al [2008]. The raw temperature profiles have an independent height resolution of about 1 km in the upper troposphere and lower stratosphere.…”
Section: Data Sets and Analysis Proceduresmentioning
confidence: 99%